2005
DOI: 10.1039/b312177c
|View full text |Cite
|
Sign up to set email alerts
|

Hierarchical self-assembly of columnar aggregates

Abstract: Biology often uses hierarchical self-assembly to produce complex functional structures from smaller components. At each level of this stepwise process, non-covalent interactions bring together the subunits of a lower level of complexity, using the information encoded in their structures. Applying this approach to synthetic systems represents a formidable challenge, because it requires a high degree of command of non-covalent interactions. In this tutorial review, recent developments in the hierarchical self-as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
80
0
3

Year Published

2005
2005
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 160 publications
(83 citation statements)
references
References 36 publications
0
80
0
3
Order By: Relevance
“…The macromolecular helicity memory of poly-1 assisted by the interaction with an achiral diamine 15 lasted for over six months as observed for the helical PCPA, PPPA, and PEPPA with a helicity memory after the SEC fractionation, 31,[35][36][37][38] but the memory gradually declined with time at ambient temperature (20)(21)(22)(23)(24)(25) C) and the ICD intensity of the fractionated poly-1 showed a decrease of about 20% at room temperature after 185 d. The stability of the memory was highly dependent on the concentration of the salts and the decreasing rate was accelerated in the presence of the common salts; the ICD completely disappeared after 12 h in the presence of 15 . TosOH ([15 .…”
Section: Homentioning
confidence: 99%
See 1 more Smart Citation
“…The macromolecular helicity memory of poly-1 assisted by the interaction with an achiral diamine 15 lasted for over six months as observed for the helical PCPA, PPPA, and PEPPA with a helicity memory after the SEC fractionation, 31,[35][36][37][38] but the memory gradually declined with time at ambient temperature (20)(21)(22)(23)(24)(25) C) and the ICD intensity of the fractionated poly-1 showed a decrease of about 20% at room temperature after 185 d. The stability of the memory was highly dependent on the concentration of the salts and the decreasing rate was accelerated in the presence of the common salts; the ICD completely disappeared after 12 h in the presence of 15 . TosOH ([15 .…”
Section: Homentioning
confidence: 99%
“…Constructing artificial helical polymers [1][2][3][4][5][6][7][8][9][10][11][12][13] and oligomers (foldamers) [14][15][16][17][18] or supramolecular helical assemblies [19][20][21][22][23][24][25] with controlled helicity has attracted significant interest in recent years in the fields of polymer and supramolecular chemistry because of their potential applications for novel chiral materials. In a series of our studies, we reported the helicity induction in optically inactive, cis-transoidal poly((4-carboxyphenyl)acetylene) (PCPA), [26][27][28][29] poly((4-phosphonophenyl)acetylene) (PPPA), [30][31][32] and poly(ethyl(4-ethynylphenyl)phosphonate) (PEPPA) 30,31,33,34 ( Figure 1) with chiral amines in dimethyl sulfoxide (DMSO) and some amino acids in water.…”
mentioning
confidence: 99%
“…123, 144912 ͑2005͒ chiral discotics, where the discotic polymers hierarchically self-assemble to form long one-dimensional columns. 2 We have derived a master equation for the reactions and diffusion of the rods on a lattice, focussing on the special case in which the system remains homogeneous, which corresponds to the reaction-limited scenario. This is equivalent to the mean-field description that is commonly used to study living polymers.…”
Section: -11mentioning
confidence: 99%
“…Another important example of equilibrium polymers is given by self-assembled stacks of discotic molecules, 1,2 which have possible applications in plastic transistors and photovoltaics. A large number of studies on the equilibrium properties of equilibrium polymers have been published, both theoretical 3,4 and experimental; 5,6 for recent reviews on this subject see Refs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation